Influence of antihypertensive pharmacological treatment on the acute cardiovascular responses to the resistance exercise in hypertensive middle-aged women - Gilene de Jesus Pereira; Rodrigo Miguel-; Valter Joviniano de Santana-Filho; José Augusto Soares Barreto-Filho; Cristiane Kelly Aquino dos Santos; Mylena Maria Salgueiro Santana; Marcelo Mendonça Mota; Tharciano Luiz Teixeira Braga da Silva; Silvan Silva de Araujo; José Carlos Tavares Junior; Rogério Brandão Wichi (Universidade Estadual Paulista (UNESP), 2020)
Abstract Aim: To investigate the hypothesis that the resistance exercise (RE) may be safer if the blood pressure (BP) is properly controlled through antihypertensive pharmacological treatment in hypertensive middle-aged women. Methods: The final sample was comprised of 19 hypertensive women, with an average age of 58±5 years and a body mass index of 29±5 Kg/m2. They were divided into three groups: controlled (n=6), uncompensated (n=8), and untreated (n=5). The subjects from all groups were submitted to a test of maximal strength on extensor chair and held a session of RE (knee extension, 3x12 to 60% 1RM) and the cardiovascular response (BP and heart rate) was monitored continuously by photoplethysmography during exercise and until five minutes after exercise (recovery). Results: Systolic BP (SBP) and diastolic BP (DBP) responses were lower in the controlled group compared to the other groups (p<0.05). The heart rate was not different between groups, while the double product was lower in the controlled group compared to the untreated group (p<0.05). The SBP and DBP peaks were lower in the controlled group compared to the other groups (p<0.05). Conclusion: The BP increases significantly during RE when the hypertension is not controlled. Pharmacological control was shown to be effective in preventing the increase of BP during the performance of the RE.